2002
DOI: 10.1128/jcm.40.11.4235-4243.2002
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Ovine Enzootic Abortion by Enzyme-Linked Immunosorbent Assay with a Recombinant Protein Fragment of the Polymorphic Outer Membrane Protein POMP90 ofChlamydophila abortus

Abstract: Ovine enzootic abortion (OEA) resulting from infection of sheep and goats with Chlamydophila abortus is of major economic importance worldwide. Over the last 50 years the serological diagnosis of infection has been based mainly on the complement fixation test (CFT), which lacks both sensitivity and specificity because of cross-reactive antibodies to other gram-negative bacteria, including another common chlamydial pathogen of sheep, Chlamydophila pecorum. In the present study, a series of overlapping recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 36 publications
(44 reference statements)
2
75
0
4
Order By: Relevance
“…Recombinant antigens are to date not widely used in veterinary chlamydial serology and there is no general agreement as to which proteins are best for sensitivity and specificity (Longbottom et al, 2002). The 40 kDa MOMP is the immunodominant antigen at the chlamydial surface known to induce a strong humoral immune response (Caldwell et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant antigens are to date not widely used in veterinary chlamydial serology and there is no general agreement as to which proteins are best for sensitivity and specificity (Longbottom et al, 2002). The 40 kDa MOMP is the immunodominant antigen at the chlamydial surface known to induce a strong humoral immune response (Caldwell et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…abortus as antigens was described which allows to differentiate Ch. abortus antibodies in ovine sera (Longbottom et al, 2002). A serodiagnostic test combining species-specific recombinant proteins from different chlamydial species could have the inherent capability of discriminating serologically infections on the species level.…”
Section: Introductionmentioning
confidence: 99%
“…The autors state that the choice of recombinant POMP fragment has a great impact on specificity and sensitivity of the test, as in a previous study wide variation was demonstrated when assessing overlapping recombinant fragments of the POMP90 protein (Longbottom et al, 2002). No current published data is available on the test performance of the ID Screen ELISA, making comparisons difficult.…”
Section: Salmonella Enterica Serovar Abortusovis Chlamydophila Abortmentioning
confidence: 99%
“…Amplification of the truncated p91Bf99 gene fragment (p91Bf99s), cloning, expression, and purification of the glutathione S-transferase (GST) fusion protein have been described previously in detail (15). Primers and plasmid construction of the 12 200-to 300-bp overlapping fragments representing the entire gene for POMP90, as well as cloning into pGEX-4T-1 and expression as GST fusion proteins, have been published recently (16). GST was also expressed from the empty vector (i.e., no insert) as a control.…”
Section: Cell Culture Mccoy Cells (Americanmentioning
confidence: 99%